USING THE POLICY ANALYSIS MATRIX TO EVALUATE THE ECONOMIC POLICY OF TOMATO AND POTATO CROPS IN EGYPT - Mohammed* O.A (The Union of Arab Universities, 2020)
Agricultural policy in Egypt has tended in recent years to make some structural changes in order to maximize the economic return in light of the technical possibilities and local and international economics of agricultural production determinants. some Food crops, industrial and export important in Egypt, and is a source of agricultural income, In order to determine the features of agricultural price policy for most important vegetable crops in Egypt, it was possible to calculate the matrix of agricultural policy analysis, to clarify the extent of deviation of lacal market prices for tomato and potato crops and world prices to identify the levels of distortions in the commodity markets and the degree of nonemployment of resources, as well as the calculation of the nominal and effective protection factors. To identify the price policies adopted by the state, whether the policy of subsidies or taxation of producers of agricultural crops, as well as the calculation of the cost factor of the local resource to determine the comparative advantage. We conclude from the above and based on the results of the Matrix of Agricultural Policy Analysis for Tomato and Potato Crops in Egypt during the average period (2011-2017) that the country’s productive policy during the study period had any affection crop producers represented in tax rate 14.742, 12.489 pounds. Which do not compare with the support provided to them, which averaged about 93,189 pounds per acre, respectively. Tomato and potato crops have an advantage that can be used to increase their exports in the global markets, which require integration between the state and the private sector to activate the ability of crop producers to export. And Egyptian potatoes, and on this the study recommends the necessity of improving the prices of production requirements for the crops under study in a manner commensurate with the continuous increase in production costs in order to work on increasing farm income and addressing negatives arising from C Tax of SAT in high production costs and made available at affordable prices.